Blue emitting BCNO phosphors with high quantum yields1. Issue 14 (14th April 2015) - Zhang, Xinghua; Lu, Zunming; Liu, Hui; Lin, Jing; Xu, Xuewen; Meng, Fanbin; Zhao, Jianling; Tang, Chengchun
<x xml:space="preserve">Abstract</x> Blue emitting BCNO phosphors with very high quantum yields.